How institutions evolve: The political economy of skills in Germany, Britain, the United States, and Japan - Thelen, Kathleen Ann (Cambridge University, 2013)
Using case studies from Germany, Britain, the United States and Japan, this text traces cross-national differences in contemporary training regimes back to the political settlement achieved among employers in skill-intensive industries, artisans and early trade unions in the 19th century.